Control method of robotic arm integrating PID feedforward compensation and SAC algorithm - Yu, Shuang; Chen, Wei; Li, Jian; Zhou, Xin (Engineering Research Express, 2025)
To solve the problems of response lag and limited generalization of a single algorithm in traditional control methods for robotic arm trajectory tracking, a hierarchical control architecture is proposed. The upper layer adopts a soft actor critic algorithm optimized by multi actor critics to generate robust trajectories. The lower layer achieves precise tracking through the sparrow search algorithm proportional integral derivative feedforward compensation controller. The results show that the improved soft actor critic algorithm achieves average reward values of 1165 and 1087 in obstacle free scenes, with success rates of 88.65% and 83.54%, respectively, which are superior to other compared algorithms. Meanwhile, the root mean square error of the algorithm in different scenarios is only 0.18 rad s−1 and 0.24 rad s−1, respectively, and the single trajectory time is only 0.68 s and 0.77 s, achieving high-precision and high-efficiency robust trajectory generation. In addition, the sparrow search algorithm proportional integral derivative feedforward compensation controller has the highest degree of joint angle tracking coincidence, and its Z-axis contact force fluctuates around the expected value, with a lower fluctuation range than other methods, ranging from 6.78 N-7.36 N in scenario 1 and 6.52 N-8.13 N in scenario 2. This architecture achieves the synergy of global optimization and precise tracking, suitable for 3–6 axis serial industrial robotic arms, providing important reference for high-precision trajectory tracking of multi degree of freedom robotic arms.